Sustainable solution for alien algae management to reduce the environmental consequences of sea and river transport - Mateescu, C; Dima, A; Marin, D (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
The accelerated development of sea and river transport over the past few decades has led to a negative phenomenon regarding the invasion and development of alien algal species, threating to modify the ecosystem functions. Algae are an attractive feedstock for biofuels production due to many advantages such as rapid growth, chemical composition rich in lipids, carbohydrates and proteins, but also because algae do not require farmland and do not create controversy in using arable land for energy purpose to the detriment of food-intended crops. Indigenous or alien algal biomass has been excessively developed in the Black Sea basin and areas affected by eutrophication, causing environmental problems. This paper presents a sustainable management solution for mitigating the negative impact of alien algae by exploiting their energy potential for producing biogas. An innovative concept of tubular bioreactor for biogas production was developed within INCDIE ICPE-CA and could be successfully applied to harness algal biomass and produce biogas for domestic and industrial use, while simultaneously ensuring sanitation of sea shore and fresh water streams.